PENGARUH SUHU DAN WAKTU EKSTRAKSI DENGAN GELOMBANG ULTRASONIK TERHADAP AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN JAMBU BIJI (Psidium guajava L.) - Sekarsari, Sandra; Widarta, I Wayan Rai; Jambe, Anak Agung Gede Ngurah Anom (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 3 (2019): Jurnal ITEPA, 2019)
This research was conducted to determine temperature and time extraction with ultrasonic waves on the antioxidant activity of guajava leaf extract and obtain the temperature and extraction time with ultrasonic waves that are appropriate to produce the highest antioxidant activity . The experimental design used in this research was a Factorial Completely Randomized Design with time treatment consisting of 3 levels, namely 10 minutes, 20 minutes and 30 minutes and temperatures consisting of 3 levels, namely 40°C, 45°C and 50°C. The treatment was repeated two times, so that 18 experimental units were obtained. Data were conducted using analyzed of variance and if treatment had a significant effect, followed by Duncan's test. The results showed that the interaction between temperature and time of extraction of guajava leaves with ultrasonic waves had a very significant effect (P<0.01) on yield, total phenol, total flavonoids, total tannins and antioxidant activity of guajava leaves. The treatment of extraction temperature and extraction time of guajava leaves with ultrasonic waves had very significant effect (P<0.01) on yield, total phenol, total flavonoids, total tannins and antioxidant activity of guajava leaves. The best results showed that temperature of 45 o C with time 20 minutes result antioxidant activity based on 89.03 %, free radical inhibition percentage with IC 50 values 3.55 mg/L, yield 16.26 %, total phenol was 331.77 mgGAE/g extract, total flavonoids was 637.33 mgQE/g extract and total tannins were 583.75 mgTAE/g. Keywords : antioxidant, guajava leaves , temperature, time, ultrasonic s